Control by cations of opioid binding in guinea pig brain membranes. - Paterson, S J (1986)
In membrane suspensions from guinea pig brain or cerebellum, NaCl, LiCl, NH4Cl, and KCl inhibit the equilibrium binding at 25 degrees C of the selective mu-agonist [3H][2-D-alanine,4-methylphenylalanine,5-glycinol]enkephalin ([D-Ala2,MePhe4,Gly-ol5]EK), the selective delta-agonist [3H][2-D-penicillamine,5-D-penicillamine]enkephalin ([D-Pen2,D-Pen5]-EK), and the selective kappa-agonist [3H]dynorphin A-(1-9). Choline chloride inhibits mu- and kappa-binding but not delta-binding. The relative activities of these monovalent salts and the slopes of the dose-response curves are site-dependent. Binding at the kappa-binding site is also inhibited by CaCl2, MnCl2, and MgCl2. On the other hand, these divalent salts potentiate delta-binding, and MnCl2 and MgCl2 have both potentiating and inhibitory effects on mu-binding; CaCl2 inhibits but does not potentiate mu-binding. Thus, the mechanisms by which monovalent cations inhibit opioid binding differ from those of divalent cations, and the mechanisms of action of both monovalent and divalent cations may differ at each site. When the antagonist [3H]naloxone, rather than the agonist [3H][D-Ala2,MePhe4,Gly-ol5]EK, is used to label the mu-binding site, the main effect of NaCl is to potentiate binding; a 22-fold higher concentration of LiCl is required to inhibit binding. The effects of NH4Cl, KCl, MnCl2, MgCl2, CaCl2, and choline chloride are little changed when [3H]naloxone is the ligand.